Structural Alterations in a Rat Model of Short-Term Conductive Hearing Loss Are Associated With Reduced Resting State Functional Connectivity - Manno, Francis A. M.; An, Ziqi; Kumar, Rachit; Wu, Ed X.; He, Jufang; Feng, Yanqiu; Lau, Condon (Frontiers in Systems Neuroscience, 2021)
Conductive hearing loss results in attenuation of air conducted sound reaching the inner ear. How a change in air conducted sound alters the auditory system resulting in cortical alterations is not well understood. Here, we have assessed structural and functional magnetic resonance imaging (MRI) in an adult (P60) rat model of short-term conductive hearing loss (1 week). Diffusion tensor imaging (DTI) revealed fractional anisotropy and axial diffusivity alterations after hearing loss that circumscribed the auditory cortex. Tractography found the lateral lemniscus tract leading to the bilateral inferior colliculus was reduced. For baseline comparison, DTI and tractography alterations were not found for the somatosensory cortex. To determine functional connectivity changes due to hearing loss, seed-based analysis (SBA) and independent component analysis (ICA) were performed. Short term conductive hearing loss altered functional connectivity in the auditory cortex and inferior colliculus, but not the somatosensory cortex. The results present an exploratory neuroimaging assessment of structural alterations coupled to a change in functional connectivity after conductive hearing loss. The results and implications for humans consist of structural-functional brain alterations following short term hearing loss in adults.